2021
DOI: 10.48550/arxiv.2105.11639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpolating between multi-center microstate geometries

Masaki Shigemori

Abstract: We study interpolation between two multi-center microstate geometries in 4d/5d that represent Lunin-Mathur geometries with circular profiles. The interpolating solution is a Lunin-Mathur geometry with a helical profile, and is represented by a 2-center solution with a codimension-2 source. The interpolating 2-center solution exhibits interesting features such as some of the charges being delocalized, and some of the charges getting transferred from the codimension-2 center to the other, codimension-3 center as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…We observed that the CFT states described by our solutions contain examples of states that interpolate between certain types of different three-charge microstates that have recently attracted attention, expanding upon the classes of states discussed in [82,83].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…We observed that the CFT states described by our solutions contain examples of states that interpolate between certain types of different three-charge microstates that have recently attracted attention, expanding upon the classes of states discussed in [82,83].…”
Section: Discussionmentioning
confidence: 78%
“…Second, our bulk solutions do not differentiate between the polarizations of the long strands, so the same bulk solutions describe interpolations between different pairs of fractionally spectral flowed states. In this sense our bulk description is more coarse-grained than that of [83]. Nevertheless, we have found the bulk description of interesting examples of states of the general form (4.41), allowing us to describe a partial interpolation between strands that have different amounts of spectral flow.…”
Section: Interpolating Between Different Microstatesmentioning
confidence: 94%
See 3 more Smart Citations